MULTINATIONALS ENTERPRISES INFLUENCE ON ACCOUNTING IN ROMANIA - Carmen NISTOR; Monica PUIU (SEA: Practical Application of Science, 2013)

(untitled)
Economic globalizations, development of international markets, have led multinational companies to develop their activities worldwide. In this context, they faced different accounting regulations of various countries. Therefore, based on the need for a common framework of accounting regulations, several bodies have started the process of creating a System of International Accounting Standards (IAS/IFRS). The purpose of this article is to explain how multinational activities (but not only that) have influenced the process of accounting harmonization in Romania and convergence of the national accounting system to International Accounting Framework, by adopting IAS/IFRS.